DETECTION OF CELL-PROLIFERATION IN TISSUE-SECTIONS - Bacchi, C. E.; Gown, A. M. (Associação Brasileira de Divulgação Científica (ABRADIC), 1993)
1. Cell proliferation is of interest since abnormal cell proliferation appears to be a precursor of tumorigenesis and also because the quantitative description of cell proliferation in tumors can be used to predict the biological behavior of a particular neoplasia.2. Them am several reliable methods of studying cell proliferation in tissues. One of the most important is the detection of the Ki67 defined antigen in frozen sections. The number of cells expressing Ki67 correlates with histological grades of tumors and can also be predictive of clinical outcome. The Ki67 can be localized in tissue sections using monoclonal antibodies in association with the immunoperoxidase technique.3. Proliferating cell nuclear antigen (PCNA) is a component of DNA polymerase-delta and is another important cell proliferation marker manifesting a striking increase in concentration during the S phase of the cell cycle. 19A2 and PC10 are two different monoclonal antibodies which can be employed to detect PCNA in paraffin-embedded tissues.4. Molecular biology has also been making a great contribution to the study of cell proliferation. The most recent innovation in tissue identification of proliferating cells is the use of in situ hybridization for the localization of histone H3 and/or H4 mRNA. H3 mRNA-positive cells appear to be present in basal cells of the skin and in crypt cells of the intestine which are sites with high proliferation rate.
Keywords: CELL PROLIFERATION; IMMUNOHISTOCHEMISTRY; CELL CYCLE MARKERS